Evaluation of the demand for adherence to Influenza vaccination among pregnant women in primary care in the municipality of Campo Grande, in the State of Mato Grosso do Sul (MS) (Research, Society and Development, 2025)
Objectives: To evaluate vaccination coverage and adherence against Influenza among pregnant women in Campo Grande - MS from 2018 to 2023. Characterize pregnant women in the sociodemographic context of Campo Grande - MS. Methods: The sample is probabilistic, simple random. A data collection form was used and applied to pregnant women in basic units in the city of Campo Grande, Mato Grosso do Sul. Sociodemographic data, influenza vaccination coverage during pregnancy, reasons for refusing or accepting the influenza vaccine were evaluated. Results: 103 pregnant women participated, at any gestational period, randomly covering the sociodemographic profile of the interviewees. Conclusion: The Influenza virus and its high propagation capacity raise concerns about adherence to vaccination, especially in pregnant women. Most report having knowledge about vaccination, but only adhere after medical advice, prioritizing it during the gestational period.